The Effect of Brand Strategy and Pricing in Increasing Customer Loyalty of Electric Cigarette - mutia cita; Derriawan; Lola Fitria Sari (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
This study aims to explore the influence of Product Quality, Brand Image and Price on Customer Satisfaction and Customer Loyalty in e-cigarette products. This study identified that the largest number of e-cigarette users are in the age range of 21-30 years (Generation Z). The main factors that influence customer satisfaction and loyalty among this generation include product quality, brand image, and price. This is due to the tendency of Generation Z to be very sensitive to product quality, brand trust, and price considerations in making purchasing decisions. This study uses a qualitative approach by conducting in-depth interviews with regular e-cigarette consumers and analyzing customer satisfaction and loyalty towards e-cigarette products. The findings show that quality products affect customer satisfaction and loyalty, in addition, a positive brand image, supported by a good product image and user image will form strong brand values, quality products with a strong brand image will affect customer satisfaction and loyalty if the product has a competitive price, contributing significantly to customer satisfaction and loyalty. The practical implications of this study are the importance of product quality, brand image and price as a strategy to increase long-term customer satisfaction and loyalty in e cigarette products in the Indonesian cigarette industry. This study also needs to know that there needs to be quality control of a product and maintaining a positive image of a product by setting competitive prices on e-cigarettes is very helpful in increasing the satisfaction and loyalty of e-cigarette customers. Customer satisfaction and loyalty are investments from an industry to expand the target market of a product.